2011
DOI: 10.3109/03639045.2011.584192
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of lung-targeting ceftiofur-loaded gelatin microspheres

Abstract: Cef-MS is a promising alternative form with high lung-targeting properties for the treatment of respiratory infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…Burst release of approximately 5.0% was observed upon incubation of the nanoformulation to the PBS pH 7.4 inferring that only small fraction of loaded S6S is associated with the surface of the GNC, while the majority of S6S is within the gelatin matrix of formed GNCs [87]. A sustained release of loaded bioactive from gelatin nanoparticles was also observed by earlier investigators, and our results are in agreement with the existing reports [69, 88]. …”
Section: Resultssupporting
confidence: 92%
“…Burst release of approximately 5.0% was observed upon incubation of the nanoformulation to the PBS pH 7.4 inferring that only small fraction of loaded S6S is associated with the surface of the GNC, while the majority of S6S is within the gelatin matrix of formed GNCs [87]. A sustained release of loaded bioactive from gelatin nanoparticles was also observed by earlier investigators, and our results are in agreement with the existing reports [69, 88]. …”
Section: Resultssupporting
confidence: 92%
“…As reported previously, particles in the size range 7-28 mm are more likely to accumulate or deposit in the lungs by mechanical ltration through the capillary bed of the lung aer intravenous administration. 98,99 Hao et al 100 prepared and demonstrated the efficiency of ceiofur-loaded gelatin microspheres with a mean diameter of 21.26 mm as a LT-DDS. Organ distribution pattern studies have shown a higher accumulation of the drug in the lungs than in any other organ (e.g.…”
Section: Effect Of Size Of Drug Delivery Vehicles On Lung-targeted In...mentioning
confidence: 99%
“…There are many reports that focus on the preparation of lung-targeted microspheres loaded with antibiotics, anticancer drugs, or glucocorticoids for the successful treatment of tuberculosis, tumors, pneumonia, and lung injury [1720]. However, few studies reported the preparation of lung targeting and sustained drug delivery microspheres for the treatment of lung fibrosis.…”
Section: Resultsmentioning
confidence: 99%